Metacognition and Self-System Among Biology Education Undergraduates at Islamic University of Riau - Idris, Tengku; Rahmat, Adi; Hidayat, Topik; Riandi, Riandi (Journal of Natural Science and Integration, 2025)
Metacognition and the self-system are critical components influencing an individual's learning success. The ability to reflect on and regulate one’s learning processes must be accurately identified and assessed to support instructional planning that enhances these skills. This descriptive study aims to examine the metacognitive abilities and self-system of fifth-semester students enrolled in the Biology Education Study Program at the Islamic University of Riau. Utilizing a survey method, data were collected from a sample of 30 students, consisting of 6 males and 24 females. The instrument, a questionnaire based on Marzano’s Taxonomy and comprising three indicators per variable, was validated through expert review. Data were analyzed using percentage-based categorization and further examined through a Pearson product-moment correlation test via SPSS 22. Results indicated that all metacognitive indicators fell into the high category, with clarity monitoring achieving the highest score (80.27%) and process monitoring the lowest (77.87%). For the self-system, examining importance and emotional response were categorized as high, while efficacy was rated moderate. A significant positive correlation was found between metacognition and the self-system (r = 0.536), with the regression equation Y = 36.662 + 0.478X. These findings suggest that students exhibit high levels of both metacognitive and self-system abilities, which are significantly interrelated.Keywords: biology education, metacognitive, self-system, undergraduate